LONG STORAGE APPLIED STUDY TO MANAGE FLOODING IN SRIWIJAYA AREA KEDIRI CITY - Dyan Eka Nurhayati (LPPM Universitas Negeri Jakarta, 2025)
The 508 meters of drainage channel in Sriwijaya street is divided in half due the railway. The flow in drainage channel is changes gradually as a result of the culverts's smaller dimension than the drainage channel's existing dimension. As a result, occured flooding area in Sriwijaya street. Long storage planning in drainage channel's main can optimizes the productivity of drainage system to manage regional flooding. The drainage channel is designed to be 1,2 m x 1,2 m to accomodate a 10-year flood discharge of 1,31 m3/sec for Trace 1 ad 0,65 m3/sec for Trace 2. Trace 1 is the main part of the Jalan Sriwijaya drainage system, that is designed to be a long storage area, because it is located upstream of the railroad culvert. Considering a volume capacity of 1808.84 m3, the long storage in Trace 1 can accommodate a maximum flood volume of 1780 m3.